Duodenal bile acids in infants with protracted diarrhoea. Issue 2 (February 1979) - Challacombe, D N; Brown, G A; Edkins, S
Abstract : Bile acids were estimated in the duodenum of infants with protracted diarrhoea and compared with those in a control group. Significantly lower levels of total bile acids were found in infants with protracted diarrhoea, a finding which may be due to ileal dysfunction. Low concentrations of total bile acids may contribute to the poor nutritional state of these patients by impairing the normal digestion and absorption of dietary fat and fat-soluble vitamins. The absence of deconjugated bile acids in the duodenal juice of most infants with protracted diarrhoea suggests that they do not contribute significantly to the pathophysiology of this disorder.